# a(x*a)=b(x-b)

## Simple and best practice solution for a(x*a)=b(x-b) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for a(x*a)=b(x-b) equation:

Simplifying
a(x * a) = b(x + -1b)
Multiply x * a
a(ax) = b(x + -1b)
Multiply a * ax
a2x = b(x + -1b)
Reorder the terms:
a2x = b(-1b + x)
a2x = (-1b * b + x * b)
Reorder the terms:
a2x = (bx + -1b2)
a2x = (bx + -1b2)
Solving
a2x = bx + -1b2
Solving for variable 'a'.
Move all terms containing a to the left, all other terms to the right.
Divide each side by 'x'.
a2 = b + -1b2x-1
Simplifying
a2 = b + -1b2x-1
Reorder the terms:
a2 + -1b + b2x-1 = b + -1b + -1b2x-1 + b2x-1
Combine like terms: b + -1b = 0
a2 + -1b + b2x-1 = 0 + -1b2x-1 + b2x-1
a2 + -1b + b2x-1 = -1b2x-1 + b2x-1
Combine like terms: -1b2x-1 + b2x-1 = 0
a2 + -1b + b2x-1 = 0
The solution to this equation could not be determined.`